2017
DOI: 10.1038/ncomms14663
|View full text |Cite
|
Sign up to set email alerts
|

Structure and assembly of scalable porous protein cages

Abstract: Proteins that self-assemble into regular shell-like polyhedra are useful, both in nature and in the laboratory, as molecular containers. Here we describe cryo-electron microscopy (EM) structures of two versatile encapsulation systems that exploit engineered electrostatic interactions for cargo loading. We show that increasing the number of negative charges on the lumenal surface of lumazine synthase, a protein that naturally assembles into a ∼1-MDa dodecahedron composed of 12 pentamers, induces stepwise expans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 67 publications
8
140
0
Order By: Relevance
“…We recently designed and evolved a negatively supercharged variant of the cage-forming enzyme Aquifex aeolicus lumazine synthase (AaLS-13) that exploits engineered electrostatic interactions to encapsulate positively charged molecules. 1315 Cryo-electron microscopy studies have revealed that AaLS-13 cages adopt an expanded 360-subunit icosahedral structure with large, keyhole-shaped pores in the cage wall, 16 explaining the rapid and quantitative uptake of cationic cargo like positively supercharged green fluorescent protein, GFP(+36). 14,17,18 The high affinity of this cationic protein for the lumen of AaLS-13 had made it a practical packaging tag for targeting diverse enzymes to the cage interior.…”
mentioning
confidence: 99%
“…We recently designed and evolved a negatively supercharged variant of the cage-forming enzyme Aquifex aeolicus lumazine synthase (AaLS-13) that exploits engineered electrostatic interactions to encapsulate positively charged molecules. 1315 Cryo-electron microscopy studies have revealed that AaLS-13 cages adopt an expanded 360-subunit icosahedral structure with large, keyhole-shaped pores in the cage wall, 16 explaining the rapid and quantitative uptake of cationic cargo like positively supercharged green fluorescent protein, GFP(+36). 14,17,18 The high affinity of this cationic protein for the lumen of AaLS-13 had made it a practical packaging tag for targeting diverse enzymes to the cage interior.…”
mentioning
confidence: 99%
“…These conclusions were later corroborated by 19 F NMR ligand perturbation studies with both 108 and 109 with B. subtilis LS. Interestingly, the 19 F NMR spectra of 117 , 119 , 120 , and 121 (Figure ) indicated that the RS binding sites were not equivalent, and the ligands were bound in three nonequivalent forms. This result was puzzling because one might expect that the association of three identical subunits would result in a symmetrical protein with identical binding sites.…”
Section: Nuclear Magnetic Resonance Studiesmentioning
confidence: 99%
“…Thus, inhibitors of these enzymes are an attractive target for the rational design of antimicrobial agents (Scheme ) . Recent developments in nanotechnology and bioengineering have elucidated the scope of LS as a biomedical application tool, including for vaccine development, nanoparticle‐based targeted drug delivery, and protein‐delivery material …”
Section: Introductionmentioning
confidence: 99%
“…For instance, AaLS‐13, an evolved variant that possesses a negatively supercharged lumenal surface, reversibly encapsulates positively charged cargo proteins at rates approaching the diffusion limit . Cryo‐electron microscopy (EM) analysis revealed that AaLS‐13 self‐assembles into a 39‐nm icosahedrally symmetric hollow sphere composed of 72 pentamers . Partially assembled AaLS‐13 pentamers have also been used to create multilayered shell structures …”
Section: Figurementioning
confidence: 99%
“…Thus, in contrast to many viral proteins that only form shelled structures comparable in size to their native capsid, AaLS‐13 can apparently adapt to the templating NP and assemble into quasi‐spherical structures of various dimensions. The spontaneous radius of curvature of the AaLS‐13 pentamers, as well as malleable interactions between adjacent subunits, might account for the formation of such shells. Although icosahedrally symmetric assemblies are possible, nonicosahedral arrangements of pentamers covering the NPs are perhaps more likely .…”
Section: Figurementioning
confidence: 99%